Soil Erosion Estimation of Wadi Medjerda in Algeria Using the Revised Universal Soil Loss Equation (RUSLE) through GIS - Allaoui Karima; Mansouri Rachid; Dorbani Meriem (Selected Scientific Papers: Journal of Civil Engineering, 2023)
Water erosion is a major problem in the semi-arid environments of Algeria. In this vein, the objective of this study is to use the Revised Universal Soil Loss Equation (RUSLE) on the watershed of Medjerda which is located at the extreme of the North-Eastern part of the Algerian territory. Based on the crossing of various factors in raster mode under ArcGIS allows the production of diverse thematic maps corresponding to multiple factors: erosivity of precipitations, erodibility of soils, topography, the vegetal cover and the anti-erosive practices. Moreover, the risks’ map of water soil erosion was obtained depending on the combination of the previous thematic maps with four class risks has been made up indicating an average erosion value of 2.68 t/ha/year. However, this value is relatively reasonable in relation to the given rate by the interpretation of the bathymetric measures carried out in the Ain Dalia dam.